Language exposure and phonological short-term memory as predictors of majority language vocabulary and phonological awareness in dual language learning. Issue 2 (28th March 2021) - Vaahtoranta, Enni; Suggate, Sebastian; Lenhart, Jan; Lenhard, Wolfgang
Abstract: Previous work suggests that child-internal and -external factors influence dual language learning (DLL), although more work is needed – to clarify the role of phonological short-term memory (PSTM) and language exposure in particular. Accordingly, we investigated the role of language exposure and PSTM in phonological awareness and receptive and expressive vocabulary development in the majority language in DLL. PSTM was measured with both a language-specific and language-universal nonword repetition task (NWR). Sixty-five DLL preschoolers were assessed twice, five months apart. Results show that maternal majority-language proficiency as well as language-specific and universal NWR predicted all outcomes, whereas length of exposure to the majority language only predicted receptive and expressive vocabulary. Current exposure did not predict any outcome. The findings extend previous research on child-internal and child-external factors as predictors of DLL to phonological awareness and language-universal NWR.